REVIEW ON THE MONOGRAPH BY T.A. ANIKEEVA “LEGENDS OF KORKUT. OGHUZ HEROIC EPOS AS A SOURCE ON THE HISTORY OF THE TURKIC PEOPLES OF CENTRAL ASIA OF THE IX-XI CENTURIES” - Zajcev, Il'a Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2018)
Recently published in the academic publishing house “Oriental Literature” under the heading of the Institute of Oriental Studies of the Russian Academy of Sciences, T.A. Anikeeva’s monograph is dedicated to the only monument of the book epic of the Oghuz Turks – “The book of my grandfather Korkut”. The main plot-forming core around which the twelve legends of this epic are grouped is the struggle of the Turks against non-Muslims in the lands of Asia Minor, as well as numerous feuds among the Oghuz themselves. Both the addition of legends and their cyclization took quite a long time, approximately from the IX – X centuries (when the Oghuz tribes had just begun their migration to the West from Central Asia) until their written fixation, which occurred much later. Thus, the “Kitab-i dedem Korkut” can be considered one of the most important sources on the social and cultural life of the Oghuz Turks in the Middle Ages. According to T.A. Anikeeva, “in the «Book of my grandfather Korkut» reflected the events of the early Turkic semi-legendary history, and later, associated with the spread of their power in Asia Minor and contacts with Byzantium”.